5.8‐inch QHD flexible AMOLED display with enhanced bendability of LTPS TFTs. Issue 4 (16th April 2018) - Lee, Jaeseob; Nguyen, Thanh Tien; Bae, Joonwoo; Jo, Gyoochul; Lee, Yongsu; Yang, Sunghoon; Chu, Hyeyong; Kwag, Jinoh
Abstract: By applying the curve‐type thin film transistor (TFT) with longitudinal strain, TFT parameters do change little down to the 2R bending. The mobility variation range reduces down to 4% compared with 28% of the line‐type channel with transverse strain. The smaller variation is preferred for a high quality display. We clarified that majority carrier's effective mass and scattering rate are dominant factors influencing the bended TFT's performance, which can be controlled by the strain orientation and channel shape. This understanding and improvement was embedded in the 5.8″ flexible QHD active matrix organic light emitting diode panel with multi edge curvature of Galaxy S8. Through this achievement, we made our flexible premium active matrix organic light emitting diode panels more performable, reliable, and highly productive in small R bending circumstance. Abstract : By applying the curve‐type channel with longitudinal strain, the mobility variation reduces down to 4% compared with 28% of the line‐type channel with transverse strain in 2R bended TFTs. We suggest that majority carrier's effective mass and scattering rate are dominant factors influencing the bended TFT's performance, which can be controlled by the strain orientation and channel shape.